Pengaruh Model Project Based Learning (Pjbl) Berbantuan Media Nearpod terhadap Kemampuan Menulis Teks Drama Siswa : The Influence of the Project-Based Learning (Pjbl) Model Assisted by Nearpod Media on Students' Drama Text Writing Ability - Elia Maynita Karo-karo; Martua Reynhat Sitanggang Gusar; Elza Leyli Lisnora Saragih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the effect of implementing the Project-Based Learning (PjBL) model with Nearpod media on the drama writing skills of eleventh-grade students at SMK Telkom 1 Medan in the 2024/2025 academic year. This research was motivated by students' low drama writing skills, which are caused by a lack of varied learning methods and minimal use of interactive media. The research method employed was quantitative, with an experimental approach using a One-Group Pretest-Posttest Design. The study population included all 205 eleventh-grade students, while the sample consisted of 36 students selected as the experimental group. Data were collected through drama writing ability tests before and after the treatment, then analyzed using normality tests, homogeneity tests, and t-tests. The results showed a significant improvement in students' drama writing skills after implementing the PjBL model with Nearpod. The average pretest score was 65.83, with a standard deviation of 10.03, and increased to 81.38, with a standard deviation of 8.70, in the posttest. The hypothesis test shows that the calculated t-value is greater than the t-table value (0.7300 > 0.6669), so it is concluded that the implementation of the PjBL model assisted by Nearpod has a significant effect on students' drama text writing skills. This model has been proven effective in enhancing creativity, collaboration, and student engagement during the learning process. Therefore, the combination of PjBL and Nearpod is recommended as an innovative learning strategy to improve students' writing competencies at the vocational education level.